The Role of Teacher Competency, Independent Curriculum, and Management Information Systems, to improve the Quality of Education - Reni Silviah (Siber International Journal of Sport Education, 2024)
The Role of Teacher Competence, Independent Curriculum, and Management Information Systems on the Quality of Education. The aim is to analyze the role of teacher competence, independent curriculum, and management information systems on the quality of education. The method of writing this scientific article is by using the library research method, which is sourced from online media such as Google Scholar, Mendeley, and other online media. The results of this study are: 1) Teacher Competence plays a role in the Quality of Education, 2) Independent Curriculum plays a role in the Quality of Education, 2) Management Information Systems plays a role in the Quality of Education. Apart from these 2 exogenous variables that influence the endogenous variable of the Quality of Education, there are still many other factors including the environment, principal, organizational culture.